Memorandum of understanding between Universiti Teknologi MARA and The Institution of Engineers, Malaysia / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Institution of Engineers will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.